Farmers Characteristics in Planting Onion and Non-onion (Allium Ascalonicum L.) at Rejoso District of Nganjuk Regency - Nurvia, Lia; Hidayati, Dwi Ratna (HABITAT, 2017)
Nganjuk is one of the central production areas of onion with 140.22 tons production in 2014. It has contributed as much as 11.84% to the national onion production. On the other hand, SISKAPERBABO mentioned that onion has fluctuated price. However, the fluctuating price of onion does not seem to affect the onion farmers. It is proved by an increase of onion data production in Nganjuk rather than other substitute commodities. The research aims to know the characteristic of farmers in planting onion and non-onion commodity at Rejoso District of Nganjuk Regency. The data used in this research is primary data, and respondents are divided into two categories namely onion farmers (30) and non-onion farmers (30). It is analyzed using descriptive qualitative. Research result shows that both onion and non-onion farmers are in productive age (15-55 years), income of onion farmers are mostly >30.000.000 meanwhile non-onion farmers are <15.000.000, the educational background of onion farmers are mostly Senior High School, and non-onion farmers are mostly have not graduated elementary school, the majority of the experience of onion farmers and non-onion farmers ranged between 15- 30 years and land area of both are < 0.5 Ha.